Analisa Peranan dan Fungsi Public Relation Baitulmaal Munzalan Indonesia Dalam Publikasi Gerakan Infaq Beras Jakarta - Mareta Puri Rahastine (Jurnal Komunikasi, 2021)
The Jakarta Rice Infaq Movement Community is a social or non-profit organization under the auspices of the Indonesian Baitulmaal Munzalan. Which aims to help Santri, orphans and Al-Qur'an memorizers to meet their food needs, especially the need for rice as a staple food in Indonesia. This program provides good quality rice assistance and is given on a monthly basis. To increase trust in donors and potential donors, information and promotions must be carried out through various media. The promotional media commonly used by the Jakarta Rice Infaq Movement Community is through websites, events, social media and brochures so that the Rice Infaq Movement activities are increasingly known. In this study, the authors used a descriptive qualitative method which was carried out by means of direct observation and in-depth interviews with informants and then the data were analyzed descriptively. This study contains how the PR of Baitulmaal Munzalan Indonesia has a role and function in the publication of the Rice Infaq Movement in Jakarta.Keywords: Rice Infaq Movement, Publication Media, Public Relations